PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH INTERGOVERMENTAL REVENUE, UKURAN PEMERINTAH DAERAH DAN LEVERAGE TERHADAP KINERJA KEUANGAN PEMERINTAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH PERIODE TAHUN 2011-2013 (Students' Journal of Accounting and Banking, 2015)
This study aims to examine the influence of Local Taxes, Levies, Intergovernmental Revenue, Local Government Size and Leverage for Financial Performance Regency / City in Central Java province Period 2011-2013. The data used is data Local Taxes, Levies, Intergovernmental Revenue, Local Government Size, Leverage and Financial Performance in the Government of Regency / City Central Java. Samples were obtained as much as 76 data. The research data were then tested by multiple linear regression. The results showed that: Local tax positive effect on the financial performance of the government. Levies positive effect on the financial performance of the government. Intergovernmental Revenue has no effect on the financial performance of local governments. Size of Local Government has positive influence on the financial performance of the government. Leverage local governments have no effect on the financial performance of local governments.Keywords: Local Taxes, Levies, Intergovernmental Revenue, Local Government Size, Leverage and Financial Performance Government